Osman Reşer’in 1925-1934 yılları arasında Leipzig Üniversitesi Kütüphanesi’ne sattığı islam yazmaları - DOĞAN AVERBEK, GÜLER (My University, 2022)
Born in Stuttgart in 1883, Oskar Rescher was a prolific Orientalist of the 20th century. He lived in both Germany and Istanbul from 1909 to 1925 and settled down in Turkey in 1925. He studied many manuscripts found in private collections, libraries, and second-hand bookstores and sold thousands of manuscripts to various libraries, book antiquarians, and persons in Europe and America. Although the details have yet to be uncovered, Rescher’s manuscript sales are still talked about in certain circles; however, his manuscript trade has not been the subject of any study until ours. This article, which constitutes the fourth phase of a series of studies, draws attention to the 262 manuscripts Rescher sold to the Leipzig University Library between 1925-1934 and provides a list of these manuscripts after discussing the sales process. Thus, this study intends to direct attention to the 262 manuscripts one Orientalist scholar personally selected, evaluated, and sold. As in the example of the Berlin State Library, instead of sending the ordinary manuscripts that could be found almost anywhere, Rescher examined each manuscript and offered the ones that he found valuable in terms of content or physical characteristics. The prices he assigned were very reasonable, and there were librarians in Leipzig who think the future of these manuscripts is in danger and who attempt to collect as many manuscripts as possible. The list that has been organized with respect to the acquisition dates and numbers of each manuscript specifies the titles and author names. The list also provides the shelf numbers.

1883’te Stuttgart’ta dünyaya gelen şarkiyatçı Osman Reşer (Oskar Rescher), 1909-1925 yıllarında Almanya-İstanbul arasında bir hayat sürmüş, 1925’te Türkiye’ye yerleşmiştir. Türkiye’de özel koleksiyonlarda, kütüphanelerde ve sahaflarda bulunan pek çok yazmayı incelemiş, binlerce yazmayı Avrupa ve Amerika’daki muhtelif kütüphanelere, sahaflara ve şahıslara satmıştır. Detayları söylenmemekle birlikte Reşer’in yazma satışı belli muhitlerde dillendirilegelmiş; fakat –bizim çalışmalarımıza kadar- onun yazma ticareti herhangi bir çalışmaya konu olmamıştır. Bir dizi çalışmanın dördüncü safhasını teşkil eden bu makalede, Reşer’in 1925-1934 yıllarında Leipzig Üniversitesi Kütüphanesi’ne sattığı 262 yazma ele alınmış, satış prosedürü hakkında bilgi verildikten sonra yazmaların listesi sunulmuştur. Dolayısıyla bu çalışma, bir şarkiyat âliminin bizzat seçtiği, değerlendirdiği ve sattığı 262 yazmayı ilim âleminin dikkatine sunma amacındadır. Berlin Devlet Kütüphanesi örneğinde olduğu gibi burada da Reşer, hemen her yerde bulunabilen sıradan yazmaları göndermek yerine her yazmayı incelemiş, muhteva veya fizik açısından kıymetli bulduğu yazmaları teklif etmiştir. Tayin ettiği bedeller çok uygundur. Karşı tarafta ise bu yazmaların geleceğinin tehlikede olduğunu düşünen ve mümkün olduğu kadar çok sayıda yazma toplamaya çalışan kütüphaneciler mevcuttur. Yazmaların kütüphaneye dâhil oldukları tarih ve numaraya göre tertip edilen listede her bir metnin adı ve müellifi belirtilmiş, ayrıca yazmaların raf numaraları verilmiştir. .
The Islamic Manuscripts oskar rescher sold to the Leipzig University library between 1925-1934
Keywords: Sosyal ve Beşeri Bilimler; Tarih; İlahiyat; Kütüphanecilik; Dil ve Edebiyat; Türk Dili ve Edebiyatı; Doğu Dilleri ve Edebiyatları; Sanat; Social Sciences and Humanities; History; Theology; Library Sciences; Philology; Turkish Language and Literature; Eastern Languages and Literatures; Art; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; Sosyal Bilimler Genel; DİN; EDEBİYAT; TARİH; SANAT; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; SOCIAL SCIENCES, GENERAL; RELIGION; LITERATURE; HISTORY; ART; INFORMATION SCIENCE & LIBRARY SCIENCE; Information Systems and Management; Museology; Literature and Literary Theory; Visual Arts and Performing Arts; Religious Studies; Library and Information Sciences; Social Sciences & Humanities; Oskar Rescher; Osman Reşer; yazma ticareti; Leipzig Üniversitesi Kütüphanesi; İslam yazmaları; manuscript trade; Leipzig University Library; Islamic manuscripts